Studies on Dormancy Periods and Growth Rhythm of Shoot and Root of Mangosteen (Garcinia mangostana L.) - Ramdan Hidayat; Achmad Surkati; Roedhy Poerwanto; Latifah K. Darusman; Bambang S. Purwoko (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2005)
Mangosteen has a good prospectus for international market. Many people in the world like this fruit because it is delicious, has high nutrient contents, and it can be consumed as a fresh fruit. The growth of mangosteen is very slow with a very long juvenile period because of its long dormancy period. The objective of this research was to study the dormancy periods and growth rhytm of shoot and root of young and adult mangosteen seedlings. The research used completely randomized design and consisted of two experiments. The first experiment was to study the dormancy and flushing periods. The second experiment was to study the growth patterns of shoot and root foom several ages of mangosteen seedlings. This research was conducted at Mekarsari Fruit Park, Cileungsi, Bogor. The result of the experiment showed that two years old of mangosteen seedling had 5 flushes per year, four years old of mangosteen had 3-4 flushes per year, and eight years old of mangosteen only had 2 flushes. Dormancy periods were significantly different between 2,4 and 8 year of mangosteen seedling. After the seedlings have branches, the dormancy periods become twice as many as that before branching. The roots grew rapidly two weeks before flush and slower after flush occurred. Key words: Garcinia mangostana, dormancy, flush, seedling